Liposomal Formulation of a Melphalan Lipophilic Prodrug: Studies of Acute Toxicity, Tolerability, and Antitumor Efficacy - Tretiakova, Daria; Svirshchevskaya, Elena; Onishchenko, Natalia; Alekseeva, Anna; Boldyrev, Ivan; Kamyshinsky, Roman; Natykan, Alexey; Lokhmotov, Anton; Arantseva, Diana; Shobolov, Dmitry; Vodovozova, Elena (Current Drug Delivery, 2020)
Background: Recently we developed a scalable scheme of synthesis of melphalan ester conjugate with 1,2-dioleoyl-sn-glycerol (MlphDG) and a protocol for the fabrication of its lyophilized liposomal formulation. Objective: Herein we compared this new convenient in use formulation of MlphDG with parent drug Alkeran® in rats concerning several toxicological parameters and evaluated its antitumor efficacy in the model of breast cancer in mice. Method: Liposomes of approximately 100 nm in diameter, consisting of egg phosphatidylcholine, soybean phosphatidylinositol, and MlphDG, or placebo liposomes without the drug were produced by extrusion and lyophilized. Alkeran® or liposomes recovered by the addition of water were injected into the tail vein of animals. Clinical examination of rats consisted of detailed inspection of the behavior, general status, and hematological parameters. Mice with transplanted breast cancer WNT-1 were subjected to multiple treatments with the drugs; tumor growth inhibition was assessed, together with cellular immunity parameters. Results: Liposomes showed approximately two times lower acute toxicity and better tolerability than Alkeran® in terms of behavioral criteria. The toxic effects of liposomes on hemopoiesis were manifested at higher doses than in the case of Alkeran®, proportionally to the difference in LD50 values. The formulation inhibited tumor growth significantly more effectively than Alkeran®, delaying the start of the exponential growth phase and exhibiting no additional toxic effects toward bone marrow. Conclusion: Lower toxicity of the liposomal formulation of MlphDG promises improved quality of life for cancer patients in need of treatment with melphalan. Presumably, the list of indications for melphalan therapy could be extended.
Keywords: acute toxicity in rats